Measurements of B(c)+ production and mass with the B(c)+ → J/ψπ+ decay. - Aaij, R; Abellan Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2012)
Measurements of B(c)(+) production and mass are performed with the decay mode B(c)(+)→J/ψπ(+) using 0.37 fb(-1) of data collected in pp collisions at √[s]=7 TeV by the LHCb experiment. The ratio of the production cross section times branching fraction between the B(c)(+)→J/ψπ(+) and the B(+)→J/ψK(+) decays is measured to be (0.68±0.10(stat)±0.03(syst)±0.05(lifetime))% for B(c)(+) and B(+) mesons with transverse momenta p(T)>4 GeV/c and pseudorapidities 2.5<η<4.5. The B(c)(+) mass is directly measured to be 6273.7±1.3(stat)±1.6(syst) MeV/c(2), and the measured mass difference with respect to the B(+) meson is M(B(c)(+))-M(B(+))=994.6±1.3(stat)±0.6(syst) MeV/c(2).